Psychiatry trainee welfare – from words to action. (June 2019) - Kim, Hannah; Suetani, Shuichi; Forbes, Malcolm; Nguyen, David
Objective: To review selected literature available on trainee welfare and reflect on our own experiences to provide practical advice to our colleagues and suggest strategies to enhance trainee welfare. Conclusions: Promoting the welfare of psychiatry trainees requires a three-pronged approach. We must care for ourselves through individual strategies; we must advocate for optimization of the systems we work in to minimize modifiable factors associated with burnout; and we must continue on the perennial challenge of culture change to reduce stigma around stress and mental illness and promote a healthier workplace.